KARAKTERISASI STRUKTUR PATAHAN PADA LAPANGAN PANAS BUMI X (SUMATRA) BERDASARKAN PEMETAAN GEOLOGI, PENGINDERAAN JAUH, DAN DATA GAYA BERAT: FAULTS CHARACTERIZATION IN X GEOTHERMAL FIELD (SUMATRA) BASED ON GEOLOGICAL MAPPING, REMOTE SENSING AND GRAVITY DATA - Sri Mulyani; Yunus Daud; Riza G. Pasiki; Haris Siagian (Buletin Sumber Daya Geologi, 2022)
Fault structure plays an important role in a geothermal system. Faults can be weak zones that are the location of intrusions that are related with heat sources, the location of permeability for reservoar, and as the fluid flow path to the surface that appears as manifestation. By understanding the characterization and distribution of geological structures in geothermal fields, the conceptual model of geothermal systems can be better understood, so the risk of counter-inaccuracies in the development of geothermal at the subsurface can be minimized. Field X is located on the Sumatra Island, known as development field that still trying to get the optimal well location for production. This study reveals how to identify faults in Geothermal Field X using gravity data analysis, remote sensing and geological mapping results. In detail, the gravitational data analysis includes checking the quality data, calculating and mapping of the residual and regional data, FHD, SVD, and 3D gravity modelling. Remote sensing data that analysed in the form of LIDAR rendering data, data used from geological mapping results are location and strike of faults. The results of this study are model and map of the faults distribution in geothermal field X that can be used as reference to understand the geothermal system, as well as the guidance for the well targeting.